Entre duas perspectivas: a formação espacial do bairro do Passo em São Borja dentro de uma leitura de novas classes geossociais e ecológicas - (:unkn) unknown (Universidade Federal do Pampa, 2025)
This study analyzes the spatial formation of the Passo neighborhood, in São Borja (RS), from the perspective of historical-dialectical materialism and critical geography, seeking to understand the relationships between space, society, and nature within the context of the Anthropocene. Grounded in the contributions of Karl Marx, Henri Lefebvre, Milton Santos, Bruno Latour, and Nikolaj Schultz, the research interprets space as a product of social and historical relations, and territory as an expression of the contradictions between economic production and the reproduction of life. The qualitative and descriptive methodology employed bibliographical and documentary sources, including the Master Plan of São Borja (1997), the IBGE Census (2010), the SINAGEO Report (2012), AdaptaBrasil/MCTI (2024), and local academic studies. The dialectical analysis revealed that the Passo neighborhood is a historically marginalized space marked by urban precariousness and ecological vulnerability, where social inequalities overlap with environmental risks. Based on the concepts of ecological and geosocial classes proposed by Latour and Schultz (2022), the research identifies new collective subjects shaped by the interaction between material, political, and environmental conditions. The study concludes that the Passo neighborhood reflects, on a local scale, the contradictions of contemporary capitalism, highlighting the need to understand territory as a central component of social life in times of climatic crisis.
Between two perspectives: the spatial formation of the Passo neighborhood in São Borja within an interpretation of new geosocial and ecological classes
Keywords: Classes ecológicas; Educação libertadora; Espaço geografico; Ecological classes; liberating education;; Geographic space; CIENCIAS HUMANAS